THE EFFECT OF FIRM CHARACTERISTICS AND ENTREPRENEUR CHARACTERISTICS ON THE SUCCESS OF MSME BUSINESS IN CENTRAL JAVA PROVINCE - Inayah Adi Sari; Dien Novyani Rahmantika; Mahmud Yunus - (Jurnal Manajemen Dayasaing, 2021)
The objective of the article is to examine the effect of Firm Characteristics and Entrepreneur Characteristics on the success of MSME businesses in several cities/districts in Central Java Province. This research design is quantitative research. The population of MSMEs in Central Java Province was 147,220 MSMEs. The sample in this study was 100 MSMEs, determined by the simple random sampling method. The sample consisted of MSMEs that were scattering in Tegal, Pekalongan, Semarang, Kudus, Jepara, and solo areas. The research data has obtained by distributing questionnaires to business managers. Hypothesis testing uses multiple linear regression test. The results of the study that entrepreneur characteristics have a positive and significant effect on the success of MSME businesses, meanwhile firm characteristics do not have a significant effect on the success of MSME businesses. The results of the analysis related to demographic variables, only entrepreneurs who have longer business experience can get business success compared to entrepreneurs who have shorter business experience. Besides, gender is also a determining factor in the success of MSME businesses.The implication of this research is that success in business is determined by the character of the entrepreneur. Business experience and the gender of the entrepreneur will support the achievement of business success. The results of this study provide benefits for entrepreneurs to be successful and useful for policy makers related to the development of micro, small and medium enterprises.The results of this study contribute to the development of science, especially related to the theory of the development of micro, small and medium enterprises